2002
DOI: 10.1029/2001ja005086
|View full text |Cite
|
Sign up to set email alerts
|

The 8‐hour tide in the Arctic mesosphere and lower thermosphere

Abstract: [1] An all-sky VHF meteor radar at Esrange (68°N, 21°E) near Kiruna in Northern Sweden has been used to investigate the 8-hour tide in the Arctic mesosphere and lower thermosphere. We present a climatology of the 8-hour tide over the period October 1999 to April 2001. The tide appears to be a persistent feature of the Arctic atmosphere, although a large day-to-day variability of the tidal amplitude is observed. At times the 8-hour tide reaches amplitudes over 30 m s À1 . The amplitude of the tide increases wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
101
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(118 citation statements)
references
References 27 publications
(56 reference statements)
13
101
4
Order By: Relevance
“…The figure also shows a clear response at the period of the M 2 lunar tide. Note that the 6-h and 8-h tides over Esrange have been described elsewhere (Smith et al, 2004;Younger et al, 2002;Beldon et al, 2006). Figure 1b shows an expanded view of the periodogram of available spectral resolution).…”
Section: Discussionmentioning
confidence: 99%
“…The figure also shows a clear response at the period of the M 2 lunar tide. Note that the 6-h and 8-h tides over Esrange have been described elsewhere (Smith et al, 2004;Younger et al, 2002;Beldon et al, 2006). Figure 1b shows an expanded view of the periodogram of available spectral resolution).…”
Section: Discussionmentioning
confidence: 99%
“…This is the first report of terdiurnal tides observed in the nightglow measurements over the Indian subcontinent. Many previous works have reported the observations of 8 h tide in the MLT region (for example, Glass and Fellons, 1975;Teitelbaum et al, 1989;Oznovich et al, 1995Oznovich et al, , 1997Thayaparan, 1997;Taylor et al, 1999;Smith, 2000;Younger et al, 2002;Taori et al, 2005;Wu et al, 2005;Beldon et al, 2006;Jiang et al, 2009;Rao et al, 2011). Glass and Fellons (1975) and Teitelbaum et al (1989) suggested that this wave can be interpreted both as the solar driven terdiurnal tide and as the result of nonlinear interaction between diurnal and semi-diurnal tides.…”
Section: Tide-like Long Period Oscillationsmentioning
confidence: 99%
“…Smith (2000) reported the latitudinal structure and seasonal variation of the terdiurnal tides using the wind observations of HRDI instrument on-board UARS. Younger et al (2002) investigated the 8 h tidal phenomena Rao et al (2011) have reported the occurrence and variability of terdiurnal tides in the MLT region over Tiruneveli (8.7 • N, 77.8 • E), Koto Tabang (0.2 • S, 100.3 • E), and Pameungpeuk (7.4 • S, 107.4 • E) using meteor wind radar measurements. It is worthy to mention here that Tirunelveli is an equatorial station located within a distance of 9 • from Kolhapur -the site of current study.…”
Section: Tide-like Long Period Oscillationsmentioning
confidence: 99%
“…All of these radars are All-Sky Interferometric Meteor Radars (SkiYMet) (Hocking and Vandepeer, 2001). Details of the individual systems are provided by Mitchell et al (2002), Day and Mitchell (2010), and Sandford et al (2010) for the Esrange system, Singer et al (2003) and Hoffmann et al (2010) for the Juliusruh system, Fritts et al (2010Fritts et al ( , 2012 for the TdF system, and Younger et al (2002) and Mitchell and Beldon (2009) …”
Section: Meteor Radarsmentioning
confidence: 99%